2010
DOI: 10.1029/2009jd012257
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric inverse modeling to constrain regional‐scale CO2 budgets at high spatial and temporal resolution

Abstract: [1] We present an inverse modeling framework designed to constrain CO 2 budgets at regional scales. The approach captures atmospheric transport processes in high spatiotemporal resolution by coupling a mesoscale model with Lagrangian Stochastic backward trajectories. Terrestrial biosphere CO 2 emissions are generated through a simple diagnostic flux model that splits the net ecosystem exchange into its major components of gross primary productivity and autotrophic and heterotrophic respirations. The modeling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 95 publications
2
109
0
Order By: Relevance
“…Mesoscale atmospheric inversions were used in several studies as a promising tool to monitor and estimate regional flux balances at high resolution (Lauvaux et al, 2009;Schuh et al, 2010;Go¨ckede et al, 2010a). Though errors in the atmospheric transport model and at the boundaries limit the potential of the method (Go¨ckede et al, 2010b;Lauvaux et al, 2012), mesoscale inverse systems have shown consistent improvements from prior fluxes over short periods of time (Lauvaux et al, 2009), and at the annual time scale over the region (Schuh et al, 2010).…”
Section: Series B Chemical and Physical Meteorologymentioning
confidence: 99%
“…Mesoscale atmospheric inversions were used in several studies as a promising tool to monitor and estimate regional flux balances at high resolution (Lauvaux et al, 2009;Schuh et al, 2010;Go¨ckede et al, 2010a). Though errors in the atmospheric transport model and at the boundaries limit the potential of the method (Go¨ckede et al, 2010b;Lauvaux et al, 2012), mesoscale inverse systems have shown consistent improvements from prior fluxes over short periods of time (Lauvaux et al, 2009), and at the annual time scale over the region (Schuh et al, 2010).…”
Section: Series B Chemical and Physical Meteorologymentioning
confidence: 99%
“…This may explain the different sign of the modeldata discrepancies during night-time between the urban sites and the other sites. We thus restrict the remaining analyses in this paper to the period between 12:00 and 17:00 UTC, wherein we can expect the boundary layer to be well developed, to have a stable height and to exert minimum influence on the variations in gas mole fractions (Geels et al, 2007;Göckede et al, 2010).…”
Section: Co 2 Ch 4 and Mixing Layer Mean Diurnal Cyclesmentioning
confidence: 99%
“…In the United States, versions of these systems are currently operated by PSU at Ameriflux sites located in Canaan Valley (WV), Chestnut Ridge (TN), Missouri Ozarks (MO), and Mead (NE), and operated by NCAR as part of the Regional Atmospheric Continuous CO 2 Network in the Rocky Mountains (Rocky RACCOON, raccoon.ucar.edu) at Fraser Experimental Forest (CO), Niwot Ridge T-Van Site (CO), Storm Peak Laboratory (CO), Hidden Peak (UT), and Roof Butte (AZ). Instruments based on the designs described in this paper are also deployed in Oregon (Göeckede et al, 2010) and at Morgan-Monroe State Forest (IN) (Schmid et al, 2000).…”
Section: Introductionmentioning
confidence: 99%